Pengaruh Terapi Akupresure Terhadap Hyperemesis Gravidarum pada Ibu Hamil Trimester I di Puskesmas Kuala Bangka Kab. Labuhan Baru Utara Tahun 2022 - Nilan Sari; Nur Azizah; Lidya Natalia Sinuhaji; Rosmani Sinaga; Junida Laia (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Pregnancy is a physiological process that is accompanied by various changes, including hormonal changes that can cause nausea and vomiting (emesis gravidarum). One of the non-pharmacological interventions that can be used to manage these symptoms is acupressure therapy. This study aims to determine the effect of acupressure therapy on reducing symptoms of hyperemesis gravidarum in pregnant women in the first trimester at the Kuala Bangka Health Center, North Labuhan Batu Regency in 2022. This study uses a pre-experimental design with a pre-post one group design approach. The sample consisted of 20 pregnant women in the first trimester who experienced symptoms of hyperemesis gravidarum. The acupressure intervention was carried out for 3 days at PC6 and ST36 points. Measurements of nausea and vomiting levels were carried out before and after the intervention using a standard measurement scale. The results of the analysis showed that there was a decrease in the average rate of nausea and vomiting by 0.90000 after acupressure therapy was performed. The paired t-test showed a p-value of 0.000 (<0.05) and a calculated t-value of 7.285 > table 1.729, which means that there is a significant effect of acupressure therapy on reducing the symptoms of hyperemesis gravidarum. Acupressure therapy is effective in reducing the rate of nausea and vomiting in pregnant women in the first trimester.